MELECON 2008 - The 14th IEEE Mediterranean Electrotechnical Conference 2008
DOI: 10.1109/melcon.2008.4618549
|View full text |Cite
|
Sign up to set email alerts
|

Robust transmission of H.264/AVC sequences using list decoding and source constraints

Abstract: Abstract-Video compression standards commonly adopted in wireless multimedia transmission systems generally apply variable length codes (VLCs) to achieve the required datarates. The resulting bitstreams are sensitive to transmission errors which cause visual artifacts that propagate in both spatial and temporal domains, thus reducing significantly the quality of the reconstructed video sequences. This paper proposes the application of a List Decoder to improve the quality of H.264/AVC encoded sequences. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…In [7], syntax and semantic violation rules were proposed which only manage to locate 57% of the visually impaired regions. Joint Source-Channel techniques were adopted in [8] - [10]. However, the method proposed in [8] reduces the compression efficiency of the codec while the other approaches provide limited protection.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], syntax and semantic violation rules were proposed which only manage to locate 57% of the visually impaired regions. Joint Source-Channel techniques were adopted in [8] - [10]. However, the method proposed in [8] reduces the compression efficiency of the codec while the other approaches provide limited protection.…”
Section: Introductionmentioning
confidence: 99%
“…The redundancy in the compressed image and video was analysed in [30], where it was concluded that significant gain in performance can be achieved when additional video data properties are taken into consideration while decoding. Based on this observation the authors in [31,32] have implemented a modified Viterbi decoding algorithm to recover feasible video sequences [33]. Sequential decoding methods were adopted for H.264/AVC encoded sequences in [31,34] whose performance in terms of quality is similar to the results presented in [33].…”
Section: Introductionmentioning
confidence: 93%
“…As shown in Table 2, the sequence cab is present in the list F generated by the list decoder. On the other hand, if the Viterbi approach adopted in [32,33] is performed, this sequence is lost at the expense of sequences having a higher hamming distance from the received bitstream (Table 3). This is mainly because the Viterbi approach selects one partial sequence of k symbols and n bits, thus prematurely pruning a number of potentially valid sequences.…”
Section: List Decoder Strategymentioning
confidence: 99%
“…Recently, Farrugia and Debono proposed a novel error control strategy based on list decoding, which enables erroneous bits in the video slice to be corrected [5]- [7]. They showed that their method, aided by a slice structuring error resiliency technique and zero motion vector error concealment, is capable of achieving a peak signal-to-noise ratio (PSNR) gain of about 2 dB as compared to one without any error correction [7].…”
mentioning
confidence: 99%
“…Analogous to the breadth-first tree search, for a given value of M , the performance of the list decoder is heavily dependent on the length of the decoded sequence as well as the number of possible paths at each stage. The results in [5]- [7] were based on a modest size of 100 bytes per slice. Furthermore, some syntax (stages) have a high number of possible codewords (paths).…”
mentioning
confidence: 99%